Pengaruh Terapi Integrasi Sensori Motor terhadap Gejala Psikiatri Pasien Skizofrenia - Rita Untari; Hendri Kurniawan (MOTORIK Jurnal Ilmu Kesehatan, 2019)
Background Schizophrenia is one of the major mental disorders resulting in meaningful changes in the overall quality of several aspects of personal behavior. One important problem in individuals with schizophrenia is the inability to understand and interpret sensory input from the environment. One method to improve the interpretation of sensory input from the environment is the sensorimotor integration approach. Proprioceptive and vestibular problems affect poor patterns of movement, spatial awareness, fear of falling, sense of touch, visual and auditory problems due to visual, auditory and tactile problems (hallucinations and delusions), cognitive problems (delirium, information processing deficits, problems processing information, problems solving, decision making and social behavior (irritability and isolation) The purpose of this study was to determine the effect of sensorimotor integration therapy on psychiatric symptoms of schizophrenia patients in Utami Laras Rehabilitation Institution in Surakarta This study was conducted with a pre-experimental design with one group pretest-post test design Patients who met the criteria were given a pretest with the Brief Psychiatric Rating Scale (BPRS) instrument, intervening sensorimotor integration therapy, after 8 times the patient's therapy was given a post test. After 8 interventions there was a decrease in the SRB score, which means there was an improvement in the patient's psychiatric symptoms. psychiatric patients with schizophrenia decline (get better) after following sensorimotor integration therapy interventions. Sensorimotor integration therapy has a significant impact on improving psychiatric symptoms in schizophrenic patients.